Thermogravimetric Analysis of p-Hydroxy-Benzoic acid Melamine-Formaldehyde Tercopolymers - Gurnale, W.B.; Juneja, H.D.; Paliwal, L.J. (Asian Journal of Chemistry, 2010)
Polymers were prepared by the condensation of p-hydroxy benzoic [PB], melamine [M] and formaldehyde [F] in the presence of hydrochloric acid (2 M) as catalyst with varying molar ratios of reacting monomers. Polymers were characterised by their IR spectra, elemental analysis, TGA, DTA and Mn as determined by vapour pressure osmometry as well as non-aqueous conductometric titrations. The kinetic and thermodynamic parameters such as, order of reaction, energy of activation, frequency factor, entropy change, free energy change and apparent entropy change have been determined. Freeman-Carroll and Sharp-Wentworth methods have been applied for the calculation of kinetic parameters, while the data from the Freeman-Carroll method have been used to determine various thermodynamic parameters.